U(h)-Free Modules over the Lie Algebras of Differential Operators - Dilxat, Munayim; Gao, Shoulan; Liu, Dong; Xia, Limeng (Mathematics (Basel), 2022)
This paper mainly considers a class of non-weight modules over the Lie algebra of the Weyl type. First, we construct the U(h)-free modules of rank one over the differential operator algebra. Then, we characterize the tensor products of these kind of modules and the quasi-finite highest weight modules. Finally, we undertake such research for the differential operator algebra of multi-variables.